A educação musical na Assembleia de Deus Congregação Monte Sinai II em Palmas-TO - Santos, Higor Leonardo Bispo dos (Universidade Federal do Tocantins, 2024)
The present work proposes to study how the musical education process occurs in the Assembly of God Congregation Monte Sinai II in Palmas-To, covering children and adults who are inserted in this space, with this it is possible to detect the results obtained in the musical education process. To carry out this work, the methodology to be used will be based on a wide bibliographical research in the specific and related area, oral history and data collection instruments will be used, such as semi-structured interviews and participant observation. The theoretical foundation is based on Arroyo (2002), Blazina (2012), Figueiredo (2010), Freitas (2008), Kater (2004), and Queiroz (2012). In view of this, it appears that the process of music education occurs through individual rehearsals at home with the help of music-oriented applications and also rehearsals in the church with the collaboration of the leader to solve doubts, it is clear that music influences life of those who use it and it presents itself in different ways, with regard to the ways of use, and it is possible to verify that the evolution of the musicians' skills is continuous since the constant practice in their lives, also through the routine of studies and rehearsals . On the other hand, it is clear that the spiritual and social side is interconnected within this ministry, since the work provided by the church reflects on the social life of the participants. Therefore, music education within the evangelical environment is extremely relevant for the proposed study.